#TITLE_ALTERNATIVE# - CHANNEL (NIM 12005032), KEVIN
Geomorphologically, the study area consists of three geomorphology units, namely: Lava Dome Unit, Volcanic Plain Unit, and Volcanic Hills Unit. Stratigraphy of the study area is divided into five units (from the oldest to the youngest): Pangamunamun Andesite Lava Unit, Jimat Andesite Lava Unit, Nagasari Andesite Lava Unit, Pekandangan Andesite Lava Unit, and Batur Pyroclastic Fall Unit. In the study area, five craters are found and four of them shows a lineament to the north and a strike with a trend of N 14o E. The soil geochemistry study was held around Timbang Crater, Batur Plateau, Banjarnegara District, Central Java. From 128 soil samples, 22 soil samples from A horizon and 12 soil samples from B horizon were analyzed. From 22 samples taken from horizon A which had been analyzed, boron ranges from 106.80 to 577.37 ppm, mercury ranges from < 4.0x10-4 to 1.6x10-3 ppm, pH of soil ranges from 4.98 to 6.72, and the soil temperature ranges from 12.4 to 16.5 Ã‚Â°C. Based on the soil geochemistry analysis, boron, soil temperature, and pH distribution map were made. As a result, there are indications of two fractures which are different with the fracture that controled the other craters mentioned before.